2007
DOI: 10.1016/j.cellimm.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells from HIV-1 infected individuals are less responsive to toll-like receptor (TLR) ligands

Abstract: We compared TLR responsiveness in PBMC from HIV-1-infected and uninfected individuals using the TLR agonists: TLR7 (3M-001), TLR8 (3M-002) and TLR7/8 (3M-011). Activation and maturation of plasmacytoid dendritic cells (pDC)were measured by evaluating CD86, CD40 and CD83 expression and myeloid dendritic cell (mDC) activation was measured by evaluating CD40 expression. All agonists tested induced activation and maturation of pDC in PBMC cultures of cells from HIV+ and HIV− individuals. The TLR7 agonist induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 50 publications
8
61
1
Order By: Relevance
“…The results are in accordance with the previously reported by Martinson et al (2007) about the higher expression of the activation and maturation markers CD40, CD83, and CD86 on pDC, in response to TLR7/8 stimulation; but they fail to show the overexpression of these molecules in HIV-1-infected patients, compared to healthy donors. 41 In contrast, they found a decrease in IFN-a production in response to TLR7/TLR8 stimulation in HIV-1-infected patients, compared to healthy donors.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results are in accordance with the previously reported by Martinson et al (2007) about the higher expression of the activation and maturation markers CD40, CD83, and CD86 on pDC, in response to TLR7/8 stimulation; but they fail to show the overexpression of these molecules in HIV-1-infected patients, compared to healthy donors. 41 In contrast, they found a decrease in IFN-a production in response to TLR7/TLR8 stimulation in HIV-1-infected patients, compared to healthy donors.…”
Section: Discussionsupporting
confidence: 82%
“…41 In contrast, they found a decrease in IFN-a production in response to TLR7/TLR8 stimulation in HIV-1-infected patients, compared to healthy donors. 41 Interestingly, TLR stimulation can also activate CD4 + and CD8 + T lymphocytes, determined by the expression of CD38, and even induce the central memory and effector CD4 + T cells to enter into cell cycle, and after activation can also induce apoptosis in CD4 + T cells. 42 Remarkably, modulation of TLRs expression after HIV-1 infection behaved differently.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, although the median percentage of mDC expressing CD83 was increased in response to bacteria compared to the level in the medium-only control, the increase did not reach statistical significance for any of the bacteria (E. coli, P ϭ 0.44; Enterococcus, P ϭ 0.31; B. fragilis, P ϭ 0.09). It was noted that the frequency of CD83 ϩ mDC markedly increased in cultures without exogenous stimulation (medium-only control) relative to that measured directly ex vivo, resulting in high background expression, as reported by others (36).…”
Section: Resultsmentioning
confidence: 56%
“…The concentration of HIV-1 (500 ng/ml) used in this study is within the range found in the plasma of infected individuals (including children and adults), which is known to vary depending on the stage of HIV disease (44,66). Optimal concentrations of the TLR agonists (32,54,55) and AT-2 HIV-1 (54) have been determined previously. Media and matched microvesicle controls, MV-CCR5 and MV-CEMX, served as the negative controls in these experiments.…”
Section: Methodsmentioning
confidence: 99%